2013
DOI: 10.1016/j.ijrefrig.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of a paraffin-based cold storage tank

Abstract: The aim of this study is to characterize a paraffin-based cold storage tank. Novel experimental results are presented for this system which combines a significant amount of paraffin (1450 kg) immersed around 18 spiral-shaped coils disposed in counter-current flow. The paraffin has a phase-change temperature in the range 4-8 ºC as measured by a 3-layer calorimeter. Different tests have been carried out with a constant mass flow rate and supply temperature. Around 31 % of the paraffin has hardly any contact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 19 publications
1
4
0
4
Order By: Relevance
“…After PCM sensible heating subphase, the PCM phase change is observed in the range of 25 -26 °C (as expected) and, thus, the slope of internal temperatures reduce, as outcome of the phase change process. As expected and discussed in the previous literature [34,35,22] the range of phase change temperatures is hardly detectable, since the phase change process in PCM takes place in a broad range of temperatures. After melting is completed, sensible heating is observed again and the internal temperatures start increasing until T heating is reached and the charging is stopped.…”
Section: Figure 8 Instantaneous Profiles Of Temperatures (T) Power Su...supporting
confidence: 75%
“…After PCM sensible heating subphase, the PCM phase change is observed in the range of 25 -26 °C (as expected) and, thus, the slope of internal temperatures reduce, as outcome of the phase change process. As expected and discussed in the previous literature [34,35,22] the range of phase change temperatures is hardly detectable, since the phase change process in PCM takes place in a broad range of temperatures. After melting is completed, sensible heating is observed again and the internal temperatures start increasing until T heating is reached and the charging is stopped.…”
Section: Figure 8 Instantaneous Profiles Of Temperatures (T) Power Su...supporting
confidence: 75%
“…If a paraffin had been used instead of ice, this storage capacity would have been reduced at least down to values similar to those of the systems described by Torregrosa-Jaime et al [38] and López-Navarro et al [39], or to the PCM slurry systems with high PCM concentrations. Torregrosa-Jaime et al [38] first analyzed experimentally a commercial ice storage tank around 18 spiral-shaped coils, but containing the paraffin RT8. The energy density of the system could have been larger, if dead volumes in the base and center had been avoided, which represented 31%.…”
Section: Comparison To Other Tes Systemsmentioning
confidence: 94%
“…However, these systems have a lower A/V ratio, which makes the parameter (U Á A/V) equal. These PCM slurry systems have a higher energy density than the water systems, but slightly lower than some of the conventional latent systems [38][39][40][41].…”
Section: Comparison To Other Tes Systemsmentioning
confidence: 97%
“…At a specific distance between annular fins, the maximum ice formation was achieved. A novel paraffin-based cold storage system was investigated experimentally by Torregrosa-Jaime et al [4]; 1450 kg of paraffin were placed in a shell around 18 spiral-shaped coils. The results showed that during the melting process, the natural convection within the phase change material (PCM) is the dominant heat transfer mechanism.…”
Section: Introductionmentioning
confidence: 99%